5 The effectiveness of a gamified, online, beef cattle breeding simulation to increase student engagement, motivation, and learning gains. (7th December 2018) - Haag, M; LeTourneau, J; Marra, R; Patterson, D; Smith, M; Lamberson, W
Abstract: The purpose of this study was to test the effectiveness of the gamified, online, beef cattle breeding simulation, CowGames, on improving student engagement, motivation, and learning gains in an introductory Animal Science course. Students (n=110) were asked to complete an 18-question multiple choice pretest, one scenario of CowGames, reflection questions, an 18-question multiple choice posttest, and a brief survey (IRB# 2009504). Within each scenario students were assigned to one of three feedback models: guidance, suggestive, and diagnostic by the program. In the survey, we asked students about game mechanics, game design, their motivation, and their engagement. Regarding mechanics, 54% responded favorably to the addition of immediate progress feedback. For game design, 60% of students reported positively about usability and direction clarity. Finally, over 50% of students reported increased motivation and engagement when playing CowGames compared to traditional homework assignments. Students scored significantly higher on the posttest than the pretest in all feedback models (Guidance: 10.00 ± 0.51 vs 11.50 ± 0.49, P = 0.0014; Suggestive: 9.26 ± 0.46 vs 10.42 ± 0.43, P = 0.0042; Diagnostic: 10.55 ± 0.52 vs 11.85 ± 0.53, P = 0.0069) indicating increased learning gains after using CowGames. No difference was observed between feedback models. The results of this project support the integration of learning technologies such as gamified simulations into the classroom as tools to increase engagement, motivation, and learning gains. Key Words: